Exploring intrinsically disordered proteins using site-directed spin labeling electron paramagnetic resonance spectroscopy - Le Breton, Nolwenn; Martinho, Marlène; Mileo, Elisabetta; Etienne, Emilien; Gerbaud, Guillaume; Guigliarelli, Bruno; Belle, Valérie (Frontiers in Molecular Biosciences, 2015)
Proteins are highly variable biological systems, not only in their structures but also in their dynamics. The most extreme example of dynamics is encountered within the family of Intrinsically Disordered Proteins (IDPs), which are proteins lacking a well-defined 3D structure under physiological conditions. Among the biophysical techniques well-suited to study such highly flexible proteins, Site Directed Spin Labelling combined with EPR spectroscopy (SDSL-EPR) is one of the most powerful, being able to reveal, at the residue level, structural transitions such as folding events. SDSL-EPR is based on selective grafting of a paramagnetic label on the protein under study and is limited neither by the size nor by the complexity of the system. The objective of this mini-review is to describe the basic strategy of SDSL-EPR and to illustrate how it can be successfully applied to characterize the structural behaviour of IDPs. Recent developments aimed at enlarging the panoply of SDSL-EPR approaches are presented in particular newly synthesized spin labels that allow the limitations of the classical ones to be overcome. The potentialities of these new spin labels will be demonstrated on different examples of IDPs.